Aqueous resin composition for lithium ion secondary battery separator, slurry for lithium ion secondary battery separator functional layer, and lithium ion secondary battery separator

An aqueous resin composition with 6 to 20 μm organic particles simplifies the formation of adhesive and porous membrane layers on lithium ion secondary battery separators, enhancing adhesion and heat shrinkage resistance.

JP7601289B2Active Publication Date: 2024-12-17DIC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024530360
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-05-18
Publication Date
2024-12-17
Estimated Expiration
2043-05-18

AI Technical Summary

Technical Problem

Existing methods for forming adhesive and porous membrane layers on lithium ion secondary battery separators require complex work steps, necessitating a simplification for improved adhesion and heat shrinkage resistance.

Method used

An aqueous resin composition containing organic particles with a specific particle size range of 6 to 20 μm, preferably acrylic resin, is used to form a functional layer on the separator, enhancing adhesion and heat shrinkage resistance.

Benefits of technology

The composition achieves excellent adhesion to electrodes and heat shrinkage resistance, simplifying the manufacturing process and improving separator performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601289000001
    Figure 0007601289000001
  • Figure 0007601289000002
    Figure 0007601289000002
Patent Text Reader

Abstract

The present invention provides an aqueous resin composition for lithium ion secondary battery separators, the aqueous resin composition containing organic particles (A) and an aqueous medium (B), while being characterized in that the volume average particle diameter of the organic particles (A) is 6 µm to 20 µm. Since this aqueous resin composition for lithium ion secondary battery separators enables the achievement of a separator which has excellent adhesion to an electrode and excellent thermal shrinkage resistance by single coating with excellent workability, this aqueous resin composition is suitably used for lithium ion secondary battery separators.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous resin composition for a lithium ion secondary battery separator, a slurry for a functional layer, and a separator for a lithium ion secondary battery. [Background technology]

[0002] In recent years, battery components including an adhesive layer for improving adhesion between battery components and a porous membrane layer for improving heat resistance and strength have been used in secondary batteries. Specifically, an electrode formed by further forming an adhesive layer and / or a porous membrane layer on an electrode base material formed by providing an electrode mixture layer on a current collector, and a separator formed by forming an adhesive layer and / or a porous membrane layer on a separator base material are used as battery components. The adhesive layer and the porous membrane layer are usually formed by supplying a slurry composition for an adhesive layer or a porous membrane layer, which contains a component for exerting a desired function, a binder component, and a dispersion medium such as water, onto an appropriate base material such as an electrode base material or a separator base material, and drying the slurry composition.

[0003] In recent years, therefore, attempts have been made to improve the adhesive layer and the porous membrane layer provided on the substrate in order to achieve further performance improvements in secondary batteries (see, for example, Patent Document 1). This document discloses a technique in which a particulate polymer having a core-shell structure with a core part and a shell part partially covering the outer surface of the core part, and a binder containing an acrylic polymer are used to form an adhesive layer for lithium ion secondary batteries. Also, a technique in which alumina and a binder containing an acrylic polymer are used to form a porous membrane for lithium ion secondary batteries is disclosed. Then, by providing the above-mentioned porous membrane on the separator substrate, and further providing the above-mentioned adhesive layer on the porous membrane layer, the adhesion between the electrodes and the separator in the electrolyte is enhanced, and a lithium ion secondary battery with excellent low-temperature output characteristics and high-temperature cycle characteristics is realized.

[0004] However, the method for forming such an adhesive layer and a porous membrane layer on a separator requires complicated work steps, and therefore simplification has been demanded. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2015 / 064411 Summary of the Invention [Problem to be solved by the invention]

[0006] The problem to be solved by the present invention is to provide an aqueous resin composition for a lithium ion secondary battery separator, which can provide a separator having excellent adhesion to electrodes and heat shrinkage resistance in a single coating. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors conducted extensive research to solve the above problems, and as a result, discovered that the above problems can be solved by using an aqueous resin composition containing organic particles having a specific particle size and an aqueous medium, and thus completed the present invention.

[0008] That is, the present invention relates to an aqueous resin composition for a lithium ion secondary battery separator, which contains organic particles (A) and an aqueous medium (B), and is characterized in that the volume average particle diameter of the organic particles (A) is 6 to 20 μm. Effect of the Invention

[0009] By applying the slurry for a functional layer containing the aqueous resin composition for a lithium ion secondary battery separator of the present invention to a separator, a separator having excellent adhesion to the electrode and heat shrinkage resistance can be obtained, and therefore the composition can be suitably used as a separator for a lithium ion secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The aqueous resin composition for a lithium ion secondary battery separator of the present invention is an aqueous resin composition for a lithium ion secondary battery separator containing organic particles (A) and an aqueous medium (B), in which the organic particles (A) have a volume average particle diameter of 6 to 20 μm.

[0011] First, the organic particles (A) will be described. The volume average particle diameter of the organic particles (A) is 6 to 20 μm. When the volume average particle diameter is 6 μm or more, the adhesion between the obtained porous membrane layer and the separator and the electrode becomes excellent, and when the volume average particle diameter is 20 μm or less, the dispersion stability becomes excellent. In addition, the volume average particle diameter of the organic particles (A) is preferably 6 to 15 μm because the dispersion stability is further improved.

[0012] The CV value of the organic particles (A) is preferably from 0 to 80% because this further improves the adhesion between the electrodes and the separator.

[0013] The glass transition temperature of the organic particles (A) is preferably 10 to 110° C. If it is 10° C. or higher, blocking is unlikely to occur when the particles are wound around a separator roll, improving workability. If it is 110° C. or lower, the adhesion between the electrodes and the separator is further improved.

[0014] The swelling ratio of the organic particles (A) to a mixed solvent (ethylene carbonate / ethyl methyl carbonate / diethyl carbonate=40 / 20 / 40 (volume ratio at 25° C.)) used as an electrolyte is preferably 300% or less, more preferably 150% or less.

[0015] The gel fraction of the organic particles (A) in the mixed solvent is preferably 90% or more, and more preferably 95% or more.

[0016] Examples of the organic component forming the organic particles (A) include resins such as acrylic resins, epoxy resins, urethane resins, and polyester resins, with acrylic resins being preferred.

[0017] The acrylic resin can be obtained, for example, by radical polymerization of monomer raw materials such as an acrylic monomer and a vinyl monomer.

[0018] Examples of the monomer include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; unsaturated monocarboxylic acids such as (meth)acrylic acid and crotonic acid; maleic anhydride, maleic acid, itaconic anhydride, and itaconic acid. , monomers having a carboxyl group such as unsaturated dicarboxylic acids such as fumaric acid; 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxy-n-butyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-n-butyl (meth)acrylate, 3-hydroxy-n-butyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, N-(2-hydroxyethyl) (meth)acrylic Monomers having a hydroxyl group, such as amide, glycerin mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, and lactone-modified (meth)acrylates having a hydroxyl group at the end; (meth)acrylates having an amino group, such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, and N,N-diethylaminopropyl (meth)acrylate; monomers having a nitrogen atom, such as (meth)acrylamide, monomers having an N-hydroxymethylamide group, such as N-hydroxymethyl(meth)acrylamide, and monomers having an N-alkoxymethylamide group, such as N-butoxymethylacrylamide; (meth)acrylates having a glycidyl group, such as glycidyl (meth)acrylate;Polyalkylene glycol (meth)acrylates such as polyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, polybutylene glycol (meth)acrylate, and methoxypolybutylene glycol (meth)acrylate; vinyl monomers such as styrene, α-methylstyrene, paramethylstyrene, chloromethylstyrene, vinyl acetate, and (meth)acrylonitrile; tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate; monomers having an alkoxysilyl group such as vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, and 3-(meth)acryloyloxypropylmethyldimethoxysilane; and di(meth)acrylate monomers such as ethylene glycol di(meth)acrylate and propylene glycol di(meth)acrylate. These monomers may be used alone or in combination of two or more kinds;

[0019] As the monomer, it is preferable to use a crosslinkable monomer such as a monomer having an alkoxysilyl group or a di(meth)acrylate monomer, since this further improves the swelling ratio and gel fraction of the organic particles (A) in the mixed solvent.

[0020] The content of the crosslinkable monomer in the monomer raw material is preferably 0.1 to 20% by mass. If it is 0.1% by mass or more, the swelling ratio and gel fraction in the mixed solvent are improved. If it is 20% by mass or less, the adhesion between the electrodes and the separator is improved.

[0021] In the present invention, "(meth)acrylic acid" refers to either or both of acrylic acid and methacrylic acid, "(meth)acryloyl" refers to either or both of acryloyl and methacryloyl, and "(meth)acrylate" refers to either or both of acrylate and methacrylate.

[0022] The organic particles (A) having a volume average particle diameter of 6 to 20 μm can be produced by various methods. However, the suspension polymerization method is preferred because the organic particles (A) can be obtained by a simple operation without using any special additives.

[0023] Examples of a method for obtaining acrylic resin particles as the organic particles (A) by the suspension polymerization method include a method in which a mixed liquid consisting of a polymerizable monomer component containing the monomer raw material and a polymerization initiator, and an aqueous solution containing a surfactant at a critical micelle concentration (the minimum concentration at which the surfactant forms micelles in an aqueous solution) or more is stirred to prepare an emulsion, an aqueous solution containing a dispersion stabilizer is added to this emulsion to adjust the surfactant concentration to less than the critical micelle concentration, and then radical polymerization is performed at a temperature of 50 to 100°C.

[0024] Examples of the polymerization initiator include azo compounds such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), and azobiscyanovaleric acid; organic peroxides such as tert-butyl peroxypivalate, tert-butyl peroxybenzoate, tert-butylperoxy-2-ethylhexanoate, di-tert-butyl peroxide, cumene hydroperoxide, benzoyl peroxide, and tert-butyl hydroperoxide; and inorganic peroxides such as hydrogen peroxide, ammonium persulfate, potassium persulfate, and sodium persulfate. These polymerization initiators can be used alone or in combination of two or more.

[0025] The aqueous medium (B) may be water, an organic solvent miscible with water, or a mixture thereof. Examples of the organic solvent miscible with water include alcohols such as methanol, ethanol, n-propanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; polyalkylene glycols such as ethylene glycol, diethylene glycol, and propylene glycol; alkyl ethers of polyalkylene glycols; and lactams such as N-methyl-2-pyrrolidone. In the present invention, only water may be used, or a mixture of water and an organic solvent miscible with water may be used, or only an organic solvent miscible with water may be used. From the viewpoint of safety and environmental load, only water or a mixture of water and an organic solvent miscible with water is preferred, and only water is particularly preferred.

[0026] As the aqueous medium (B), it is simple and preferable to use the aqueous medium used when producing the organic particles (A) by suspension polymerization as it is.

[0027] Examples of the emulsifier include sulfate esters of higher alcohols and their salts, alkylbenzene sulfonates, polyoxyethylene alkylphenyl sulfonates, polyoxyethylene alkyl diphenyl ether ... Examples of the emulsifiers include anionic emulsifiers such as sulfuric acid half ester salts of alkyl ethers, alkyl diphenyl ether disulfonates, and dialkyl succinate sulfonates; nonionic emulsifiers such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene diphenyl ethers, polyoxyethylene-polyoxypropylene block copolymers, and acetylene diols; cationic emulsifiers such as alkyl ammonium salts; and amphoteric emulsifiers such as alkyl (amide) betaines and alkyl dimethyl amine oxides. These emulsifiers can be used alone or in combination of two or more. These emulsifiers can also be used in the critical micelle formation. The concentration is equal to or higher than the critical micelle concentration, and is preferably 0.1 to 10 times the critical micelle concentration.

[0028] The mixture of the polymerizable monomer components containing the acrylic monomer and the polymerization initiator and the aqueous solution containing the surfactant is preferably stirred while applying shear, and for example, a stirring device such as a homomixer, a high-pressure homogenizer, an ultrasonic dispersion device, a high-pressure jet type dispersion device, a static mixer, etc. By stirring while applying shear, an emulsion having a volume average particle size of 6 to 20 μm can be easily prepared.

[0029] An aqueous solution containing a dispersion stabilizer is added to the emulsion obtained as described above to make a dispersion liquid in which the concentration of the surfactant in the emulsion is less than the critical concentration of 0.01 to 1.0, and then suspension polymerization is performed to obtain the organic particles having a volume average particle size of 6 to 20 μm.

[0030] Examples of the dispersion stabilizer include water-soluble resins such as polyvinyl alcohol, polyvinylpyrrolidone, methyl cellulose, hydroxyethyl cellulose, etc. These dispersion stabilizers can be used alone or in combination of two or more kinds.

[0031] The aqueous resin composition for lithium ion secondary battery separator of the present invention contains the organic particles (A) and an aqueous medium (B), and it is preferable that the resin particles (A) obtained by the suspension polymerization method are dispersed in the aqueous medium (B).

[0032] Furthermore, if necessary, a solvent removal step can be carried out to reduce the amount of organic solvent in the aqueous resin composition of the present invention.

[0033] The aqueous resin composition of the present invention obtained by the above method preferably contains 5 to 60 mass % of the organic particles (A) relative to the total amount of the aqueous resin composition, and more preferably contains 10 to 50 mass % of the organic particles (A), because this further improves coating workability.

[0034] In addition, the aqueous resin composition of the present invention preferably contains the aqueous medium (B) in an amount of 95 to 40 mass %, more preferably 90 to 50 mass %, based on the total amount of the aqueous resin composition, in order to further improve coating workability.

[0035] The aqueous resin composition of the present invention may contain a water-soluble polymerization inhibitor such as sodium nitrite or hydroquinone, if necessary.

[0036] In addition, the aqueous resin composition of the present invention may contain, as necessary, additives such as a curing agent, a curing catalyst, a lubricant, a filler, a thixotropic agent, a tackifier, a wax, a heat stabilizer, a light resistance stabilizer, a fluorescent whitening agent, and a foaming agent, a pH adjuster, a leveling agent, a gelling inhibitor, a dispersion stabilizer, an antioxidant, a radical scavenger, a heat resistance imparting agent, an inorganic filler, an organic filler, a plasticizer, a reinforcing agent, a catalyst, an antibacterial agent, a mildew inhibitor, a rust inhibitor, a thermoplastic resin, a thermosetting resin, a pigment, a dye, an electrical conductivity imparting agent, an antistatic agent, a moisture permeability improving agent, a water repellent, an oil repellent, a hollow foam, a compound containing crystal water, a flame retardant, a water absorbent, a moisture absorbent, a deodorizer, a foam stabilizer, an antifoaming agent, an antifungal agent, an antiseptic, an anti-algae agent, a pigment dispersant, an antiblocking agent, an antihydrolysis agent, and a pigment.

[0037] The slurry for a lithium ion secondary battery separator functional layer of the present invention contains the aqueous resin composition of the present invention, non-conductive particles, and a water-soluble polymer. The slurry for a functional layer preferably contains 0.1 to 100 mass% of organic particles (A) in the aqueous resin composition and 0.1 to 100 mass% of the water-soluble polymer relative to 100 parts by mass of the non-conductive particles.

[0038] As the non-conductive particles, for example, inorganic particles or organic particles can be used, with inorganic particles being preferred.

[0039] Examples of the inorganic particles include oxide particles such as aluminum oxide (alumina), silicon oxide, magnesium oxide, titanium oxide, BaTiO2, ZrO, and alumina-silica composite oxide, nitride particles such as aluminum nitride and boron nitride, covalent crystal particles such as silicon and diamond, sparingly soluble ion crystal particles such as barium sulfate, calcium fluoride, and barium fluoride, and clay particles such as talc and montmorillonite, and among these, aluminum oxide (alumina) is preferred. These inorganic particles can be used alone or in combination of two or more kinds.

[0040] Examples of the organic particles include polyethylene, polystyrene, polydivinylbenzene, styrene-divinylbenzene copolymer crosslinked products, various crosslinked polymer particles such as polyimide, polyamide, polyamideimide, melamine resin, phenolic resin, and benzoguanamine-formaldehyde condensate, and heat-resistant polymer particles such as polysulfone, polyacrylonitrile, polyaramid, polyacetal, and thermoplastic polyimide. These organic particles can be used alone or in combination of two or more kinds.

[0041] Examples of the water-soluble polymer include cellulose-based polymers such as carboxymethyl cellulose, methyl cellulose, and hydroxypropyl cellulose, and their ammonium salts and alkali metal salts; poly(meth)acrylic acid and their ammonium salts and alkali metal salts; polyvinyl alcohol compounds such as polyvinyl alcohol, copolymers of acrylic acid or acrylic acid salts with vinyl alcohol, copolymers of maleic anhydride or maleic acid or fumaric acid with vinyl alcohol; polyethylene glycol, polyethylene oxide, polyvinylpyrrolidone, modified polyacrylic acid, oxidized starch, starch phosphate, casein, various modified starches, etc. These water-soluble polymers can be used alone or in combination of two or more kinds.

[0042] Examples of the particulate polymer include crosslinked poly(meth)acrylic acid particles, crosslinked poly(meth)acrylic acid ester particles, crosslinked polystyrene particles, copolymer crosslinked resin particles of (meth)acrylic acid ester and styrene, melamine resin particles, nylon particles, polyimide particles, polyamideimide particles, phenol resin particles, polytetrafluoroethylene particles, fluororesin particles, silicone resin particles, etc. These particulate polymers can be used alone or in combination of two or more kinds.

[0043] The functional layer in the present invention can be formed by applying the above-mentioned functional layer slurry onto a separator. The method for applying the above-mentioned functional layer slurry composition onto a substrate is not particularly limited and any known method can be used. Specifically, the application method can be a doctor blade method, a dip method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, a brush coating method, or the like. In this case, the functional layer slurry composition can be applied to only one side of the substrate or to both sides.

[0044] The method for drying the slurry composition for the functional layer on the substrate is not particularly limited and may be any known method, such as drying with warm air, hot air, or low-humidity air, vacuum drying, or drying by irradiation with infrared rays or electron beams, etc. By drying the slurry composition for the functional layer on the substrate in this manner, the separator of the present invention having a functional layer formed on the substrate can be obtained.

[0045] The adhesion between the separator of the present invention and the electrode material is preferably 10 N / m or more.

[0046] The thermal shrinkage rate of the separator of the present invention is preferably 5% or less. EXAMPLES

[0047] The present invention will now be described in more detail with reference to specific examples.

[0048] The particle size of the organic particles was measured by a laser diffraction method. Specifically, an aqueous dispersion containing organic particles (solid concentration 25% by mass) was used as a sample, and the particle size distribution (volume basis) obtained by a laser diffraction particle size distribution measuring device (Malvern Panalytical, "Mastersizer 2000") was calculated as the particle size at which the cumulative volume calculated from the small diameter side was 50%, and this was taken as the volume average particle size (μm).

[0049] The gel ratio of the organic particles to the electrolyte was determined by drying the aqueous dispersion of the organic particles at 108°C for 4 hours to remove the water, creating a film with a thickness of 300 μm. Approximately 1 g of the film piece was precisely weighed, and the mass of the film piece was designated as W0. This film piece was immersed in approximately 100 g of a mixed solvent (EC / MEC / DEC (volume mixture ratio at 25°C) = 40 / 20 / 40)) at 60°C for 72 hours. The film piece was then pulled out of the mixed solvent. The mixed solvent on the pulled out film piece was wiped off with a towel, and then vacuum dried at 108°C for 4 hours, and its mass (mass of insoluble matter) W1 was measured. The gel fraction (%) of the organic particles to the mixed solvent was calculated according to the following formula. Gel fraction in mixed solvent (%) = (W1 / W0) x 100

[0050] The swelling ratio of the organic particles in the electrolyte was measured by drying the aqueous dispersion of the organic particles at 108°C for 4 hours to remove the water, to create a film with a thickness of 300 μm. Approximately 1 g of the film piece was precisely weighed, and the mass of the film piece was designated as W0. This film piece was immersed in approximately 100 g of a mixed solvent (EC / MEC / DEC (volume mixture ratio at 25°C) = 40 / 20 / 40)) at 60°C for 72 hours. The film piece was then pulled out of the mixed solvent. The mixed solvent on the pulled out film piece was wiped off with a towel, and its mass W1 was measured. The swelling ratio (%) of the organic particles in the mixed solvent was then calculated according to the following formula. Swelling rate in mixed solvent (%) = (W1 / W0) x 100 - 100

[0051] The glass transition temperature (Tg) was calculated by weighing 10 mg of a sample into an aluminum pan, and measuring the DSC curve at room temperature and humidity with a differential thermal analyzer (TA Instruments' "QA-100") using an empty aluminum pan as a reference, at a temperature range of -100°C to 500°C, at a heating rate of 10°C / min. During this heating process, the intersection point between the baseline immediately before the endothermic peak of the DSC curve where the differential signal (DDSC) is 0.05 mW / min / mg or more appears and the tangent to the DSC curve at the first inflection point that appears after the endothermic peak was determined as the glass transition temperature (Tg).

[0052] (Example 1: Synthesis of aqueous resin composition (1)) 1.00 g of t-butyl peroxyoctoate was dissolved in a mixture of 121.4 g of styrene, 76.2 g of 2-ethylhexyl acrylate, and 2.4 g of 3-methacryloxypropyltrimethoxysilane to prepare a polymerizable monomer component. Separately, 3.00 g of alkylbenzene sulfonate ("Neogen S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was dissolved in 200.0 g of water. The above polymerizable monomer component was mixed into this aqueous solution and stirred at a rotation speed of 6000 rpm for 10 minutes using a TK Homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.). The obtained emulsion was placed in a 2 L reaction vessel equipped with a stirrer and a thermometer, and an aqueous solution in which 8.0 g of polyvinyl alcohol ("44-88" manufactured by Kuraray Co., Ltd.) was dissolved in 430.7 g of water was further added, and polymerization was carried out at 75°C for 5 hours while stirring in a nitrogen stream. The temperature was then raised to 85°C, and polymerization was carried out for 2 hours to obtain an aqueous resin composition (1). The volume average particle size of the organic particles (A-1) in the aqueous resin composition (1) was 7.2 μm.

[0053] (Example 2: Synthesis of aqueous resin composition (2)) Except for changing the rotation speed of the TK Homomixer to 3500 rpm, an aqueous resin composition (2) was obtained in the same manner as in Example 1. The volume average particle diameter of the organic particles (A-2) in the aqueous resin composition (2) was 9.5 μm.

[0054] (Example 3: Synthesis of aqueous resin composition (3)) Aqueous resin composition (3) was obtained in the same manner as in Example 1, except that 1.00 g of t-butyl peroxyoctoate was dissolved in a mixed solution consisting of 140.5 g of styrene, 57.1 g of 2-ethylhexyl acrylate, and 2.4 g of 3-methacryloxypropyltrimethoxysilane to form a polymerizable monomer component. The volume average particle diameter of the organic particles (A-3) in the aqueous resin composition (3) was 6.8 μm.

[0055] (Example 4: Synthesis of aqueous resin composition (4)) Aqueous resin composition (4) was obtained in the same manner as in Example 1, except that 1.00 g of t-butyl peroxyoctoate was dissolved in a mixed solution consisting of 121.4 g of methyl methacrylate, 76.2 g of 2-ethylhexyl acrylate, and 2.4 g of 3-methacryloxypropyltrimethoxysilane to form a polymerizable monomer component. The volume average particle diameter of the organic particles (A-4) in the aqueous resin composition (4) was 7.0 μm.

[0056] (Example 5: Synthesis of aqueous resin composition (5)) Aqueous resin composition (5) was obtained in the same manner as in Example 1, except that 1.00 g of t-butyl peroxyoctoate was dissolved in a mixed liquid consisting of 121.4 g of styrene, 76.2 g of 2-ethylhexyl acrylate, and 2.4 g of ethylene glycol dimethacrylate to form a polymerizable monomer component. The volume average particle diameter of the organic particles (A-5) in the aqueous resin composition (5) was 6.2 μm.

[0057] (Comparative Example 1: Synthesis of Water-Based Resin Composition (R1)) Except for changing the rotation speed of the TK Homomixer to 10,000 rpm, an aqueous resin composition (R1) was obtained in the same manner as in Example 1. The volume average particle diameter of the organic particles (RA-1) in the aqueous resin composition (R1) was 1.9 μm.

[0058] (Comparative Example 2: Synthesis of Water-Based Resin Composition (R2)) 1.00 g of t-butyl peroxyoctoate was dissolved in a mixture of 121.4 g of styrene and 76.2 g of 2-ethylhexyl acrylate to prepare a polymerizable monomer component. Separately, 3.00 g of alkylbenzene sulfonate ("Neogen S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was dissolved in 200.0 g of water. The above polymerizable monomer component was mixed into this aqueous solution and stirred at 8000 rpm for 10 minutes using a TK Homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.). The obtained emulsion was placed in a 2 L reaction vessel equipped with a stirrer and a thermometer, and an aqueous solution in which 8.0 g of polyvinyl alcohol ("44-88" manufactured by Kuraray Co., Ltd.) was dissolved in 430.7 g of water was further added, and polymerization was carried out at 75°C for 5 hours while stirring in a nitrogen stream. The temperature was then raised to 85°C, and polymerization was carried out for 2 hours to obtain an aqueous resin composition (R2). The volume average particle size of the organic particles (A-1) in the aqueous resin composition (R2) was 3.2 μm.

[0059] (Comparative Example 3: Synthesis of Water-Based Resin Composition (R3)) To a reactor equipped with a stirrer and a thermometer, 70 g of ion-exchanged water, 0.15 g of sodium lauryl sulfate ("EMAL 2F" manufactured by Kao Chemical Co., Ltd.) as an emulsifier, and 0.5 g of ammonium persulfate as a polymerization initiator were supplied, the gas phase was replaced with nitrogen gas, and the temperature was raised to 60°C. Meanwhile, 50 g of ion-exchanged water, 0.5 g of sodium dodecylbenzenesulfonate as an emulsifier, and 94 g of butyl acrylate, 2 g of acrylonitrile, 2 g of methacrylic acid, 1 g of N-hydroxymethylacrylamide, and 1 g of allyl glycidyl ether as polymerizable monomers were supplied to another vessel and mixed to obtain a monomer mixture. The monomer mixture was continuously added to the reactor over a period of 4 hours to carry out polymerization. During the addition of the monomer mixture, the polymerization reaction was continued at a temperature of 60°C. After the addition was completed, the mixture was stirred for another 3 hours at a temperature of 70°C to terminate the polymerization reaction, thereby obtaining an aqueous resin composition (R3). The volume average particle diameter of the organic particles (RA-3) in the aqueous resin composition (R3) was 0.3 μm.

[0060] [Preparation of slurry for functional layer] A mixture of 30.0 parts by mass of polyvinyl alcohol (DIC Corporation, "DICNAL VA-29") and 0.36 parts by mass of dispersant (Tetsutani Corporation, "BYK-154") was stirred at 1,000 rpm with a homodisper, while 30.0 parts by mass of alumina (Sumitomo Chemical Co., Ltd., "AKP-3000") was gradually added, and the mixture was dispersed for 5 minutes. After the mixture became uniform, 6.0 parts by mass of the aqueous resin composition obtained above and 15.8 parts by mass of ion-exchanged water were added, and the mixture was dispersed for 10 minutes at 5,000 rpm with a homodisper. The obtained slurry was filtered through a 100-mesh wire net to obtain a functional layer slurry.

[0061] [Separator manufacturing] The functional layer slurry was applied to a 12 μm thick polyethylene separator substrate using a bar coater to a dry thickness of 4 μm, to obtain a separator having a functional layer. The drying temperature was 80° C. and the drying time was 1 minute.

[0062] [Adhesion evaluation] The peel strength was measured as follows to evaluate the adhesion. Specifically, a test sample was prepared by bonding the negative electrode and the separator together by pressing the composite layer of the negative electrode (HS-LIB-N-Gr-001, manufactured by Hosen Co., Ltd.) and the functional layer on the separator so that they faced each other at a temperature of 80°C and a load of 6.5 MPa for 1 minute. This was cut into a piece 20 mm wide and 120 mm high, and after double-sided tape was applied to the surface of the negative electrode, it was fixed to a metal plate with the double-sided tape. One end of the test piece on the separator side was pulled vertically at a speed of 10 mm / sec to measure the stress when peeled off. The higher the peel strength value from the electrode, the more preferable it is. Equipment used: Shimadzu Autograph AG-10KNX Plus Tool used: Tensile chuck Test speed: 100mm / min Cell used: 50N Measurement temperature: room temperature

[0063] [Evaluation of heat shrink resistance] The separator coated with the functional layer was cut into 5 cm squares, the test pieces were sandwiched between cardboard, heated in a dryer with an internal temperature of 150°C for 1 hour, and then removed. The distance between the midpoints of the two opposing sides was measured and recorded as the dimension after shrinkage (mm). Using the initial dimension and the dimension after shrinkage obtained, the length in the MD direction (longitudinal direction) and the length in the TD direction (transverse direction) were calculated using the following formula, and the thermal shrinkage rate (%) was obtained from the average value. The smaller this thermal shrinkage rate value, the better. Heat shrinkage rate (%) = {initial dimension (mm) - dimension after shrinkage (mm)} / initial dimension (mm) x 100

[0064] The evaluation results of Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Tables 1 and 2.

[0065] [Table 1]

[0066] [Table 2]

[0067] It was confirmed that the separators coated with the aqueous resin compositions of the present invention according to Examples 1 to 5 had excellent adhesion to the electrodes and heat shrinkage resistance.

[0068] On the other hand, Comparative Examples 1 to 3 are examples in which the volume average particle size of the organic particles (A) is smaller than the lower limit of the present invention, but it was confirmed that the adhesion to the electrode was insufficient.

Claims

1. The aqueous resin composition for a lithium ion secondary battery separator contains organic particles (A), an aqueous medium (B), and a dispersion stabilizer (C), characterized in that the organic particles (A) have a volume average particle diameter of 6 to 9.5 μm, the volume ratio of particles having a particle diameter of 2 μm or less in the organic particles (A) is 30% or less, and the aqueous resin composition for a lithium ion secondary battery separator contains 0.1 to 20 mass % of the dispersion stabilizer (C).

2. 2. The aqueous resin composition for lithium ion secondary battery separator according to claim 1, wherein the organic particles (A) have a swelling ratio of 300% or less and a gel fraction of 90% or more in a mixed solvent (ethylene carbonate / ethyl methyl carbonate / diethyl carbonate=40 / 20 / 40 (volume ratio at 25° C.)).

3. A slurry for a lithium ion secondary battery separator functional layer, comprising the aqueous resin composition for a lithium ion secondary battery separator according to claim 1 or 2.

4. A lithium ion secondary battery separator having a coating film obtained by using the slurry for a lithium ion secondary battery separator functional layer according to claim 3.

Citation Information

Patent Citations

  • Composite diaphragm for reducing thermal runaway risk of lithium battery, preparation method and lithium battery

    CN111293262A

  • Separator for battery and battery using it

    JP2000260413A

  • Secondary battery and its manufacturing method

    JP2004241135A

  • Cell separator and cell using the same

    JP2013211160A

  • Laminate porous film and nonaqueous electrolyte solution secondary battery

    JP2019010883A